The Effect of Internet-Based Learning Media on Student Learning Outcomes in Ensemble Learning - Andika Putra, Yoga; Darma Putra , Irdhan Epria (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
The purpose of this study is to describe the addition of cultural arts learning outcomes by using internet learning media in cultural arts subjects at SMAN 1 Batipuh, Tanah Datar Regency. This instrument is made to be able to meet the data obtained from the influence of using the online learning environment. With the help of an online learning environment. This type of research is ex post facto research. The population of this study is students of grade XI Social Studies 1 SMAN 1 Batipuh for the 2022/2023 academic year. The sample was taken by proportional random sampling of 27 people. Information is collected through questionnaires. Statistical hypothesis techniques, descriptive analysis and correlation tests are used in the analysis of research materials. There is a relationship between the influence of learning interest and learning outcomes, namely rcalculate = 0.8819 > rtabel = 0.3809 which means there is a significant relationship between these variables.